A Deadline-Aware and Distance-Aware Packet Scheduling Algorithm for Wireless Multimedia Sensor Networks. (31st March 2015) - Tang, Lin; Guan, Quansheng; Jiang, Shengming; Guo, Bingyi
Abstract : We propose a wireless differentiated queuing service (WDQS) algorithm to meet the diverse delay requirements in wireless multimedia sensor networks (WMSNs). WDQS adopts novel latest departure time (LDT) scheduling criteria to differentiate forwarding emergency by considering the packets' lifetime, the known delay it has already experienced, and the remaining delay it will experience. We also propose an effective approach to estimate the unknown delay for the remaining journey without any message overhead by exploiting the query mechanism of the sink. We further discuss analytically the packet's lifetime setting to meet the end-to-end (e2e) delivery requirement. The simulation results verify our analytical discussion and show performance improvements in terms of e2e delay and packet drop rate.